Topology of the effectively paired and unpaired electron densities for complex bonding patterns: The three-center two-electron bonding case - Lobayan, Rosana Maria (2009)
Our previously reported local formalism of the electron density decomposition into effectively paired and unpaired densities is applied to electron deficient molecular systems possessing complex bonding patterns. It is shown that the unpaired density is not only near the nuclear positions, like in classical bonds, but also spills out over the bonding regions, to compensate the electron deficiency. Topological information obtained from the effectively unpaired density, which may not be directly observed from the total density, allows us to establish a procedure to detect complex interactions. This study is complemented with results arising from nonlocal formalism of topological population analyses. The conclusions from both formalisms are in complete agreement and permit to interpret the well-known structural information from Lipscomb styx numbers going beyond it in cases where the electronic description becomes ambiguous, pointing out the subtle information contained in the unpaired density. Numerical results for three-center two-electron bondings in the boranes B2H6, B4H10, B5H9, and B5H11 are reported. © 2009 American Chemical Society.